Intention, barriers and opportunities to exit from commercial sex work among female sex workers in Ethiopia: Qualitative study - Mazeingia, Yohannes Teka; Negesse, Ayenew (International Journal of Occupational Safety and Health, 2020)
Background: Commercial sex work exposed women to countless risks and exit is recommended as an essential strategy to tackle those risks. Intention to exit can predict women’s actual exit potential from commercial sex work. Therefore, the purpose of the study was to explore intention, barriers and facilitating situations to exit from commercial sex work among female sex workers in Dire Dawa, Ethiopia.Method: We conducted qualitative research among 18 female sex workers using in-depth interviews. Once data was collected with the local language, we transcribed the recorded data and translated to English before exporting to ATLASti7 to facilitate the data analysis process. We used respondent-driven sampling to recruit study participants. We implemented the inductive thematic analysis approach.Result and discussion: Women had a strong intention to exit from commercial sex work. Although women intended to give up on commercial sex work, they needed to pass barriers like financial insecurity, social stigma and discrimination, skill gap, lack of support and poor education status before they successfully exit. Their demand for minimal financial supports to open a private business and strong motivation are opportunities for a successful exit from commercial sex work.Conclusion: Women had a strong intention to exit from commercial sex work though they demanded support from others. Therefore, government and other stakeholders need to provide comprehensive support to commercial sex workers like financial support, fill skill gap and improve poor saving habit through training and establish functioning rehabilitation centers for drug addict women.